The Association Between Vena Cava Implantation Technique and Acute Kidney Injury After Liver Transplantation. Issue 11 (November 2020) - Hannon, Vivienne; Kothari, Rishi P.; Zhang, Li; Bokoch, Michael P.; Hill, Rachel; Roll, Garrett R.; Mello, Anna; Feiner, John R.; Liu, Kathleen D.; Niemann, Claus U.; Adelmann, Dieter
Abstract : Background: Acute kidney injury (AKI) after liver transplantation is associated with increased morbidity and mortality. It remains controversial whether the choice of vena cava reconstruction technique impacts AKI. Methods: This is a single-center retrospective cohort of 897 liver transplants performed between June 2009 and September 2018 using either the vena cava preserving piggyback technique or caval replacement technique without veno-venous bypass or shunts. The association between vena cava reconstruction technique and stage of postoperative AKI was assessed using multivariable ordinal logistic regression. Causal mediation analysis was used to evaluate warm ischemia time as a potential mediator of this association. Results: The incidence of AKI (AKI stage ≥2) within 48 h after transplant was lower in the piggyback group (40.3%) compared to the caval replacement group (51.8%, P < 0.001). Piggyback technique was associated with a reduced risk of developing a higher stage of postoperative AKI (odds ratio, 0.49; 95% confidence interval, 0.37-0.65, P < 0.001). Warm ischemia time was shorter in the piggyback group and identified as potential mediator of this effect. There was no difference in renal function (estimated glomerular filtration rate and the number of patients alive without dialysis) 1 y after transplant. Conclusions: Piggyback technique, compared with caval replacement, was associated with a reduced incidence of AKI after liver transplantation. There was no difference in long-term renal outcomes between the 2 groups.